Web buckling of high‐strength steel plate girders induced by bending curvature. Issue 2 (16th April 2020) - de Deus Nascimento, Sérgio Marcelo; Pedro, José J. Oliveira; da Graça, André Filipe Biscaya Semedo Pereira
Abstract: Professor Eduardo de Arantes e Oliveira Award at XII Conference on Steel and Composite Construction in Coimbra 2019 The simplified formula for the web slenderness limit given in EN 1993‐1‐5 to prevent flange‐induced buckling does not usually govern the web design other than for very slender class 4 plate girder webs in steel grades S235 to S355. However, the same formula applied to plate girders designed in S690 high‐strength steel (HSS) gives lower slenderness limits likely to govern web design and restrains the possibilities for reducing their thickness in order to profit from the high steel resistance. This paper reviews the background to the simplified formula currently used and compares the web slenderness limits obtained with numerical results from a full non‐linear analysis of slender high‐strength steel girders.